2009
DOI: 10.1068/p6250
|View full text |Cite
|
Sign up to set email alerts
|

Anger and Happiness are Linked Differently to the Explicit Detection of Biological Motion

Abstract: The detection of biological motion and the detection of emotion from this motion are important visual functions with obvious survival and social values. The perception of biological motion is remarkably robust, and numerous studies have shown that the emotional states of a person can be deduced from point-light biological motion. In the present study, we investigated the extent to which the detection of emotion from biological motion is linked to the explicit detection of human gait. Subjects performed gait de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 46 publications
7
32
1
Order By: Relevance
“…Beyond the overall enhancement of biological motion detection, the authors found that the presence of anger in the movement had a uniquely facilitative effect on the detection of biological motion. Similarly, Ikeda & Watanabe (2009) reported that discriminability of biological motion was enhanced when it contained emotional content. Thus, the presence of emotional components in human movement seems to aid in its detection and provide salient distal cues for subsequent social behavior.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Beyond the overall enhancement of biological motion detection, the authors found that the presence of anger in the movement had a uniquely facilitative effect on the detection of biological motion. Similarly, Ikeda & Watanabe (2009) reported that discriminability of biological motion was enhanced when it contained emotional content. Thus, the presence of emotional components in human movement seems to aid in its detection and provide salient distal cues for subsequent social behavior.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, human movement cues can be detected at a distance, out of an immediate social interactional range. In other words, an individual’s gait or body movements can provide rich, proximal and distal information in the way of social communication (Barclay et al 1978; Dittrich et al 1998; Ikeda & Watanabe, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Differences between the perception of happy and angry interactions have been widely reported in the neuroimaging and multisensory literature (e.g. Massaro and Egan, 1996; Fox et al, 2000; Ikeda and Watanabe, 2009). From a practical perspective, it was also easier for our actors to perform happy and angry interactions and for us to create scenarios to help them demonstrate these emotions.…”
Section: Discussionmentioning
confidence: 96%
“…we are “standing up for the body” (de Gelder et al, 2010) and exploring body language reading in typical (Atkinson et al, 2004, 2012; Chouchourelou et al, 2006; Ikeda and Watanabe, 2009; Alaerts et al, 2011; Sokolov et al, 2011; Krüger et al, 2013; Actis-Grosso et al, 2015; de Gelder et al, 2015; for review, see Pavlova, 2017) and atypical development (e.g., Nackaerts et al, 2012; Strauss et al, 2015; Van den Stock et al, 2015; Vaskinn et al, 2016; Blain et al, 2017). …”
Section: Yes Look At Behavior!mentioning
confidence: 99%